2021
DOI: 10.1021/acs.iecr.1c02175
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Modeling Study on the Pretreatment and Alkaline Hydrolysis of Blue Agave Bagasse in Twin-Screw Extruders

Abstract: A recent mathematical model describing the pretreatment and alkaline hydrolysis of lignocellulosic biomasses in twin screw extruders (TSEs) is used to study the deconstruction and degradation of blue agave bagasse (BAB), an important waste biomass from the Tequila industry, in a laboratory-scale extruder. This pretreatment process using TSEs is technologically important. Experiments using NaOH for the delignification, extraction, and partial hydrolysis of hemicellulose and cellulose were performed. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…There have hitherto been developed various pretreatment strategies regarding the productivity, yield, and number of steps to enhance the hydrolysis of lignocellulose materials. Over the past few years, pilot-scale operational conditions have been proposed for alkaline [ 34 , 35 ], hydrothermal [ 36 ], and ultra-fast hydrolysis by supercritical CO 2 pretreatments. More recently, Ferri et al [ 6 ] demonstrated a robust and eco-friendly three-step biorefinery process for the efficient release of FA.…”
Section: Resultsmentioning
confidence: 99%
“…There have hitherto been developed various pretreatment strategies regarding the productivity, yield, and number of steps to enhance the hydrolysis of lignocellulose materials. Over the past few years, pilot-scale operational conditions have been proposed for alkaline [ 34 , 35 ], hydrothermal [ 36 ], and ultra-fast hydrolysis by supercritical CO 2 pretreatments. More recently, Ferri et al [ 6 ] demonstrated a robust and eco-friendly three-step biorefinery process for the efficient release of FA.…”
Section: Resultsmentioning
confidence: 99%
“…There have hitherto been developed various pretreatment strategies regarding the productivity, yield, and the number of steps to enhance the hydrolysis of lignocellulose materials. Over the last years, pilot-scale operational conditions have been proposed for alkaline [37,38], hydrothermal [39], and ultra-fast hydrolysis by supercritical CO2 pretreatments. More recently, Ferri et al [6] demonstrated a robust and eco-friendly three-step biorefinery solution for the efficient release of FA.…”
Section: Release Of Fa From Bran Using Enzyme-assisted Hydrolysis Of 10-and 30-fold Scale-up Processmentioning
confidence: 99%
“…Others have reported alkaline decomposition kinetics of lignin model compounds (Gierer et al, 1977;Shimizu et al, 2012;Shimizu et al, 2013), although these insights are not readily extensible to real biomass, where cell wall biopolymer assemblies and tissue pore structures at the nanoscale and mesoscale, respectively, heavily influence experimental kinetic measurements (Min et al, 2014;Lima et al, 2018). Indeed, given the complexity surrounding experimental diffusion measurements (Jakes et al, 2020), few reports attempt to quantify the significant mass or heat transfer effects that accompany deacetylation of real biomass (Costanza and Costanza, 2002), especially as they apply to complicated continuous reactor configurations such as packed corn stover beds (Sahayaraj et al, 2021) or twin-screw extruders (Morales-Huerta et al, 2021). Lastly, the vast majority of these studies employ whole (unsorted) corn stover as the feedstock, despite the known structural and compositional differences among its major anatomical fractions (Min et al, 2014), which are expected to imbue unique kinetic and physical transport properties.…”
Section: Introductionmentioning
confidence: 99%